Future expectations of adolescents from different social backgrounds - Fornell, Pilar; Ortiz-Bermúdez, Amaranta Úrsula; Rodríguez-Mora, Álvaro; Verdugo, Laura; Sánchez-Sandoval, Yolanda (Anales de Psicología / Annals of Psychology, 2023)
This paper analyzes adolescents’ future expectations (FE) and their relationship with personal variables (age, sex, self-esteem, and life satisfaction) and contextual variables (perceived social support and level of risk). The sample includes 748 adolescents, aged 9-16 (M = 11.93, SD = 1.42), coming from contexts with different levels of social risk. The results show that FE decrease as age increases, with few differences found based on sex. More positive self-perceptions and perceived social support are associated with better FE. Concerning the level of risk, more vulnerable contexts have a higher negative effect on FE. The regression analysis reveals the predictive capacity of the studied variables. The structural equation model confirms the positive causal effect of psychological adjustment and perceived social support, as well as the negative influence of contexts with greater social disadvantages on adolescent FE. The results suggest the need to establish preventive programs aimed at promoting personal resources of children, especially those who come from vulnerable contexts.